Mentoring generation Z in finding Who Am I - Purwandari, Eny; Pertiwi, Deni Santi; Aryono, Sischa; Pujiono, Ragil; Azizah, Siti Nur (Universitas Muhammadiyah Magelang, 2021)
Generation Z teenagers from birth have been in contact with technology, so that their activities become easier and faster. However, adolescence is a time when self-concept needs to be developed. Self-concept is influenced by experiences and the social environment in which the teenager is friends. The purpose of this community service is to introduce the importance of self-concept to Generation Z teenagers at SMA Muhammadiyah Al Kautsar Special Program, Kartasura. Activities carried out using the lecture method accompanied by assignments in the form of open questionnaires and group interviews. The result of this community service shows that the self-concept of teenagers is quite positive. In general, participants' perceptions of self-identification were easy to get along with, brave, and confident. The participants also believed in their own abilities as indicated by an optimistic attitude towards the future.